Pelatihan Fungsi Khusus Pada Excel Untuk Peningkatan Ketrampilan Di Yayasan Budi Pakarti Nusantara Tangerang - Arsanto Narendro; Suwasti Broto; Tatang Wirawan Wisnuadji (CV. Multi Kreasi Media, 2025)
Many employees in the company have not optimally mastered Excel formulas and functions, which hinders work efficiency and data-driven decision-making. This training is designed with an interactive approach, including both theoretical sessions and hands-on practice. Participants are provided with material on basic formulas, logical functions, and data analysis using Excel. Evaluations are conducted through quizzes and practical assignments to measure participants' understanding. After attending the training, 85% of participants showed an improvement in their ability to use Excel formulas and functions, based on the evaluation results before and after the training. Participants also reported increased confidence in completing tasks that require data analysis. This training successfully enhanced employees' skills in using Excel, positively impacting productivity and work quality. Recommendations for further training and regular monitoring are necessary to ensure these skills continue to develop.